Do Better Committee Assignments Meaningfully Benefit Legislators? Evidence from a Randomized Experiment in the Arkansas State Legislature. Issue 2 (25th March 2015) - Broockman, David E.; Butler, Daniel M.
Abstract: A large literature argues that the committee assignment process plays an important role in shaping legislative politics because some committees provide legislators with substantial benefits. However, evaluating the degree to which legislators benefit from winning their preferred assignments has been challenging with existing data. This paper sheds light on the benefits legislators accrue from winning their preferred committee assignments by exploiting rules in Arkansas' state legislature, where legislators select their own committee assignments in a randomized order. The natural experiment indicates that legislators reap at most limited rewards from winning their preferred assignments. These results potentially raise questions about the robustness of widely held assumptions in literatures on party discipline and legislative organization.